2011
DOI: 10.1037/a0020784
|View full text |Cite
|
Sign up to set email alerts
|

Head Start and urban children's school readiness: A birth cohort study in 18 cities.

Abstract: We used longitudinal data from a birth cohort study, the Fragile Families and Child Wellbeing Study, to investigate the links between Head Start and school readiness in a large and diverse sample of urban children at age 5 (N = 2,803; 18 cities). We found that Head Start attendance was associated with enhanced cognitive ability and social competence and reduced attention problems but not reduced internalizing or externalizing behavior problems. These findings were robust to model specifications (including mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 79 publications
5
84
2
Order By: Relevance
“…Although studies of Head Start programs yielded overall positive effects on short term indicators of children's cognitive skills and achievement, with average effect sizes of +0.27, those studies in which the children in the control group experienced other forms of center-based care yielded significantly smaller effects as compared to those studies of Head Start in which control group children received no additional services (see also Duncan and Magnuson, 2013, for a broader discussion of the counterfactual problem). Zhai et al (2011) find a similar result using longitudinal data from the Fragile Families and Child Wellbeing Study, concluding that impacts of Head Start were largest relative to non-center-based care.…”
Section: Heterogeneity By Alternative Care Typesupporting
confidence: 57%
“…Although studies of Head Start programs yielded overall positive effects on short term indicators of children's cognitive skills and achievement, with average effect sizes of +0.27, those studies in which the children in the control group experienced other forms of center-based care yielded significantly smaller effects as compared to those studies of Head Start in which control group children received no additional services (see also Duncan and Magnuson, 2013, for a broader discussion of the counterfactual problem). Zhai et al (2011) find a similar result using longitudinal data from the Fragile Families and Child Wellbeing Study, concluding that impacts of Head Start were largest relative to non-center-based care.…”
Section: Heterogeneity By Alternative Care Typesupporting
confidence: 57%
“…In the present study, gender was not a significant determinantamongthe cognitive readiness factors measured related to achievement in reading, math, or general knowledge. This finding is consistent with the findings of another study that examined school readiness factors among Head Start urban children (Zhai, Brooks-Gunn, & Waldfogel, 2011). In this study the researchers found that neither gender nor race/ethnicity were moderating factors that determined children's school readiness.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, most non-Head Start programs are not free and can be expensive. Perhaps reflecting these differences, past research suggests that the children who enter Head Start often differ from children who attend other types of programs, demonstrating more behavioral problems and having more disadvantaged parents (Lee, Zhai, Brooks-Gunn, Han, & Walfogel, 2014; Zhai, Brooks-Gunn, & Waldfogel, 2011). …”
Section: Differences By Type Of Preschoolmentioning
confidence: 99%